48-hour Induction of Transdermal Buprenorphine to Sublingual Buprenorphine/Naloxone: The IPPAS Method. Issue 2 (19th March 2023) - Azar, Pouya; Wong, James S.H.; Mathew, Nickie; Vogel, Marc; Perrone, Jeanmarie; Herring, Andrew A.; Krausz, Reinhard M.; Montaner, Julio S.G.; Greenwald, Mark K.; Maharaj, Anil R.
Abstract : Buprenorphine is an effective medication for the treatment of opioid use disorder. However, the traditional method of buprenorphine induction requires a period of abstinence and the development of at least moderate withdrawal, which can be barriers in starting treatment. We present the case of a hospitalized patient with opioid use disorder using unregulated fentanyl, who underwent a transdermal buprenorphine induction over 48 hours to initiate sublingual buprenorphine/naloxone on the third day. The patient experienced minimal levels of withdrawal and did not experience precipitated withdrawal. The ease of use of this novel induction method over previously published induction protocols can greatly improve the accessibility of buprenorphine for patients and healthcare staff.